Pengaruh Pemberian Pupuk Hayati Mikoriza Terhadap Pertumbuhan Tanaman Bawang Daun (Allium fistulosum L.) - S. Pulungan, Ahmad Shafwan; Rangkuti, Marlinda Nilan Sari; Malau, Elfrida; Finanta, Olyfiah; Atika, Zuhairah (CV.ITTC INDONESIA, 2023)
Leeks (Allium fistulosum L.) are a type of vegetable plant in the genus Allium which is widely cultivated in Indonesia. Scallions are also a plant that is often used as an additional spice in cooking. In general, the production of leek plants (Allium fistulosum L.) really requires a good level of soil fertility where the level of soil fertility is also determined by the microorganisms contained therein. For the living environment such as soil, the presence of microorganisms can determine the level of soil fertility and improve soil conditions. The aim of this research was to examine the effect of mycorrhizal biofertilizer on the growth of leek (Allium fistulosum L.) and determine the effect of mycorrhizal biofertilizer on the growth of leek (Allium fistulosum L.). The method used in the research was a laboratory experiment which was carried out directly by researchers at the Microbiology Laboratory, Medan State University. The results of this research were that the treatment of mycorrhizal fertilizer on leeks had 2 parameters, namely plant height and number of leaves, which had an optimal effect. Based on the average yield data from the yield table, the application of a single mycorrhizal fertilizer to red spinach plants really had a big influence on its growth, where the height and number of leaves obtained each week increased 2 times more.